Multi-Port Traction Converter for Hydrogen Rail Vehicles: A Comparative Study - Emanuele Fedele; Ivan Spina; Luigi Pio Di Noia; Pietro Tricoli (IEEE Access)
The neutral-point-clamped multiport inverter (MPI) has recently gained significant attention in compact architectures for multisource systems, where multiple sources provide power to a common load. While existing studies primarily address modulation and control issues, there is a lack of comprehensive system-level analyses that evaluate the suitability of MPI-based architectures for specific applications. This paper presents a comprehensive study on an MPI-based partial-power-processing propulsion system concept for a hydrogen-powered train. The layout, control, and operation of the MPI-based traction system is thoroughly described and validated with simulations and experiments. The VA rating, weight, and volume of the MPI-based power conversion system are estimated and compared with those of the benchmark propulsion architecture. The study indicates that the MPI-based traction architecture achieves a higher VA rating compared to the standard architecture due to the higher part count. Furthermore, a slight increase in the total weight and volume of power electronics is observed for the fuel cell train when the MPI is integrated on board. These drawbacks arise from differences in operation, energy management, and system topology between the fuel cell train and other rail vehicles for which effective size reductions enabled by the MPI have been documented in the literature.